Water Quality Assessment using Selected Macroinvertebrate Based Indices and Water Quality Index of Sungai Air Hitam Selangor - Abu Sama, Harisham; Yuzir, Muhammad Ali; Azman, Shamila (Tropical Aquatic and Soil Pollution, 2024)
A study was conducted from July to December 2022 at Sungai Air Hitam, a small tributary of the Selangor River located within the Tanjung Karang Sub-basin in Malaysia (coordinates: 3° 24' 27" N, 101° 25' 54" E to 3° 28' 14" N, 101° 26' 59" E). This confluence is situated near three major downstream water treatment plants. The study assessed six water quality parameters—pH, dissolved oxygen (DO), biological oxygen demand (BOD), chemical oxygen demand (COD), ammonia (NH3), and suspended solids (SS)—to calculate the Water Quality Index (WQI). Macroinvertebrates were sampled simultaneously using the dipping net method to obtain biotic indices for further evaluation of water quality. The results indicated that the WQI classified Sungai Air Hitam as Class III, with scores ranging from 56.9 to 64.6, suggesting the river is suitable for water supply and fisheries. However, the Biological Monitoring Working Party (BMWP) index categorized the water quality as poor, with scores between 30 and 42. Similarly, the Average Score Per Taxon (ASPT) ranged from 3.25 to 5.25, indicating pollution or environmental impact, while the Family Biotic Index (FBI) further classified the river as having poor to very poor water quality, with scores between 6.57 and 8.11. Overall, the study suggests that Sungai Air Hitam has experienced some degree of ecological degradation. These findings emphasize the need for continuous monitoring and remediation efforts to preserve and restore water quality.